2021
DOI: 10.1007/s40626-021-00214-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical pattern discrimination of Miconia plants by spectral analysis and machine learning

Abstract: In loco characterization of the bioelectrical signals of two Miconia species in the time and frequency domain suggests that the species have distinct biological patterns.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This is in line with other studies on electrome complexity [ 26 , 40 , 43 ], including some that demonstrated specific electromic signatures in pathogen-infected plants [ 28 , 46 ], bioelectric patterns of oscillations recorded in loco in Miconia sp. [ 30 ], and bioelectrical reaction of fruit petioles when fruits are chewed by caterpillars [ 32 ]. Our study now shows that low-frequency peaks likely predominate in these electromes, but higher frequency bands also exist, which is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with other studies on electrome complexity [ 26 , 40 , 43 ], including some that demonstrated specific electromic signatures in pathogen-infected plants [ 28 , 46 ], bioelectric patterns of oscillations recorded in loco in Miconia sp. [ 30 ], and bioelectrical reaction of fruit petioles when fruits are chewed by caterpillars [ 32 ]. Our study now shows that low-frequency peaks likely predominate in these electromes, but higher frequency bands also exist, which is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
“…These bioelectrical signals would be modified when plants perceive environmental signals or cues and prioritise one or some of these signals and cues over others [ 23 , 24 , 25 ]. The effect of these interactions on the electrophysiology of plants has been observed in different plant species under different conditions [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, phytosemiotics is conforted by this analysis. The aim is to find specific patterns of electrome responses highlighting the cognitive capacities of plants, especially in terms of operational mode of communication at long distance (Debono and Souza 2019;, Gimenez et al 2021). These patterns could include synchronization among electrical signals at the level of single plants (Debono 2013, Masi 2009 and discrimination of environmental stimuli or propagated defense signals (Reissig et al, 2021) This still on going methodological part related to the operability and nature of in situ mesological plasticity of plants constitutes a key point of our experimental approach.…”
Section: Plasticity: Evolutionary Biology and The Umvelt Of Plantsmentioning
confidence: 99%